Membangun Kesadaran Lingkungan Melalui Budaya Organisasi Hijau Di Sekolah Adiwiyata SDS Toan Hwa Tanjungpinang - Jalal, Abdul; Ayunda Pratiwi, Mirza; Firdiyansyah, Indra; Paramita, Bunga; Wulandari, Kiki (Program Studi Manajemen FEBM UMRAH, 2025)
The purpose of this research is to build environmental awareness through green organizational culture at sds toan hwa tanjungpinang school. The method used in this research is descriptive qualitative using data collection techniques through interviews, observation and documentation. Then the data analysis techniques used are data reduction, data presentation and conclusions. The results of this study indicate that SDS Toan Hwa Tanjungpinang has implemented a green organizational culture quite well The implementation of this green organizational culture is carried out through various programs and activities, such as: physically and mentally healthy includes the physical and mental health, of classroom students without using air conditioning to maintain air circulation, facilities that meet health standards including toilets and classrooms, routine sports activities every Wednesday morning, collaborating with health centers for health screening including dental examinations and immunizations, urging parents to provide healthy lunches for children without using disposable packaging such as sterofoam. This research is intended to find out that green organizational culture is an effective strategy to build environmental awareness in schools. The implementation of green organizational culture can increase students' awareness of the environment and encourage them to behave in an environmentally friendly manner